2020
DOI: 10.3168/jds.2019-17379
|View full text |Cite
|
Sign up to set email alerts
|

Symposium review: Big data, big predictions: Utilizing milk Fourier-transform infrared and genomics to improve hyperketonemia management

Abstract: Negative animal health and performance outcomes are associated with disease incidences that can be labor-intensive, costly, and cumbersome for many farms. Amelioration of unfavorable outcomes through early detection and treatment of disease has emphasized the value of improving health monitoring. Although the value is recognized, detecting hyperketonemia (HYK) is still difficult for many farms to do practically and efficiently. Increasing data streams available to farms presents opportunities to use data to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The use of milk mid-infrared spectroscopy to improve genomic prediction accuracy of serum biomarkers I. van den Berg, 1 * P. N. Ho, 1 T. D. W. Luke, 1,2 M. Haile-Mariam, 1 S. Bolormaa, 1 and J. E. Pryce 1,2 using milk MIR to predict these serum biomarkers, with the value of R 2 obtained through random crossvalidation ranging between 0.21 and 0.92 (Belay et al, 2017;Grelet et al, 2019;Luke et al, 2019a,b;Pralle and White, 2020). In Australia, the equations for predicting serum BHB, fatty acids, and urea were initially developed by Luke et al (2019b) and have recently been validated by Ho et al (2020), with accuracies obtained through 10-fold random cross-validation of 0.60, 0.42, and 0.87, respectively.…”
Section: Many Authors Have Reported Promising Accuracies Whenmentioning
confidence: 99%
“…The use of milk mid-infrared spectroscopy to improve genomic prediction accuracy of serum biomarkers I. van den Berg, 1 * P. N. Ho, 1 T. D. W. Luke, 1,2 M. Haile-Mariam, 1 S. Bolormaa, 1 and J. E. Pryce 1,2 using milk MIR to predict these serum biomarkers, with the value of R 2 obtained through random crossvalidation ranging between 0.21 and 0.92 (Belay et al, 2017;Grelet et al, 2019;Luke et al, 2019a,b;Pralle and White, 2020). In Australia, the equations for predicting serum BHB, fatty acids, and urea were initially developed by Luke et al (2019b) and have recently been validated by Ho et al (2020), with accuracies obtained through 10-fold random cross-validation of 0.60, 0.42, and 0.87, respectively.…”
Section: Many Authors Have Reported Promising Accuracies Whenmentioning
confidence: 99%
“…Such problems not only impair farm profitability, they also directly increase veterinary and reproductive costs (Hogeveen et al, 2011;Shalloo et al, 2014), environmental losses (Bell et al, 2013), and affect animal welfare outcomes (Oltenacu and Broom, 2010). Given the high incidence and the costs of these disorders, there has been growing interest in predicting the metabolic status of dairy cows in the early stages of lactation (see the recent review of Pralle and White, 2020). This information could either be used to help farmers make informed interventions to prevent the development of these diseases, or to generate novel phenotypes for genetic improvement purposes, most likely through genomic selection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have reported promising accuracies from using milk MIR to predict serum metabolic profiles, with the R 2 obtained through random cross-validation ranging between 0.21 and 0.92 (Belay et al, 2017;Grelet et al, 2018;Pralle et al, 2018;Benedet et al, 2019;Luke et al, 2019b). Although the initial results are promising, the models should be properly validated, preferably through external validation, before they can be implemented for farmers to use as management tools (Pralle and White, 2020). This is because random cross validation is often overly optimistic when compared with the more stringent external validation (i.e., using data from a different herd; Wang and Bovenhuis, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We did further investigations on other factors, such as differences in the interval between calving to first service and breed between herd-years, but could not find any systematic patterns. Possibly, collecting more data from a diverse portfolio of herds and production systems would improve the robustness of the models (Pralle and White, 2020). In the meantime, we recommend cautious practical application of this model until this issue is resolved.…”
Section: Resultsmentioning
confidence: 99%